Analysis of the Degree of Credibility of Witness Statement Evidence and Visum Et Repertum in Fulfilling Material Truth in the Criminal Justice System: A Qawa'id Fiqhiyyah Perspective - Salman Syafriadi Manalu (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Evidence in criminal cases is a fundamental aspect that determines whether a criminal event actually occurred and whether a defendant can be held legally accountable. Evidence is not merely a formal process, but a means to discover material truth, the primary goal of criminal justice. This requires that every piece of evidence presented be credible and capable of making a real contribution to reconstructing the criminal event. In the Indonesian criminal justice system, the principle of material truth requires judges not to stop at formal truth, but rather to carefully and thoroughly explore the facts so that the verdict rendered truly reflects the actual situation. Therefore, each piece of evidence must be critically examined, not only in terms of quantity, but especially in terms of the quality and consistency of the information provided. Witness testimony is the most frequently used form of evidence in the process of proving criminal acts. In many cases, witnesses are considered to have direct knowledge of the criminal event, so their testimony is often key in constructing the facts. However, heavy reliance on testimony is problematic because it is highly subjective. The subjectivity of testimony stems from various factors, such as limited memory, differences in perception, psychological pressure, and even emotional influence on certain parties. Witnesses may experience distortions in what they see or hear, so the information they convey may not always align with objective facts. This situation presents unique challenges to the evidentiary process.